Intrauterine LPS inhibited arcuate Kiss1 expression, LH pulses, and ovarian function in rats. Issue 5 (10th October 2022) - Magata, Fumie; Toda, Lisa; Sato, Marimo; Sakono, Takahiro; Chambers, James K; Uchida, Kazuyuki; Tsukamura, Hiroko; Matsuda, Fuko
Abstract : In brief: Uterine inflammatory diseases are a major cause of infertility in humans and domestic animals. The current findings that intrauterine lipopolysaccharide is absorbed in systemic circulation and attenuates ovarian cyclic activities could provide a basis for developing novel treatments to improve fertility. Abstract: Uterine inflammatory diseases are a major cause of infertility in humans and domestic animals. Circulating lipopolysaccharide (LPS), a bacterial endotoxin causing uterine inflammation, reportedly downregulates the hypothalamic–pituitary–gonadal axis to mediate ovarian dysfunction. In contrast, the mechanism whereby intrauterine LPS affects ovarian function has not been fully clarified. This study aimed to elucidate whether uterine exposure to LPS downregulates hypothalamic kisspeptin gene ( Kiss1 ) expression, gonadotropin release, and ovarian function. Uterine inflammation was induced by intrauterine LPS administration to ovary-intact and ovariectomized female rats. As a result, plasma LPS concentrations were substantially higher in control rats until 48 h post injection, and the estrous cyclicity was disrupted with a prolonged diestrous phase. Three days post injection, the number of Graafian follicles and plasma estradiol concentration were reduced in LPS-treated rats, while numbers of Kiss1 -expressing cells in the anteroventral periventricular nucleus and arcuate nucleus (ARC) were comparable in ovary-intact rats. Four days post injection, ovulation rate and plasma progesterone levels reduced significantly while gene expression of interleukin1β and tumor necrosis factor α was upregulated in the ovaries of LPS-treated rats that failed to ovulate. Furthermore, the number of Kiss1 -expressing cells in the ARC and pulsatile luteinizing hormone (LH) release were significantly reduced in ovariectomized rats 24 h post injection. In conclusion, these results indicate that intrauterine LPS is absorbed in systemic circulation and attenuates ovarian function. This detrimental effect might be caused, at least partly, by the inhibition of ARC Kiss1 expression and LH pulses along with an induction of ovarian inflammatory response.